2018
DOI: 10.1002/lt.25040
|View full text |Cite
|
Sign up to set email alerts
|

Cold ischemia time is an important risk factor for post–liver transplant prolonged length of stay

Abstract: Risk analysis of cold ischemia time (CIT) in liver transplantation has largely focused on patient and graft survival. Posttransplant length of stay is a sensitive marker of morbidity and cost. We hypothesize that CIT is a risk factor for posttransplant prolonged length of stay (PLOS) and aim to conduct an hour-by-hour analysis of CIT and PLOS. We retrospectively reviewed all adult, first-time liver transplants between March 2002 and September 2016 in the United Network for Organ Sharing database. The 67,426 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…We did not find any difference in readmission rates, PNF rates, early mortality, and hyperbilirubinemia between shorter and longer DAT and DWIT. Moreover, DWIT and DAT did not affect the duration of posttransplant hospitalization and readmission rates that are relevant in terms of hospital costs and resource use in health care . A previous large single‐center study (215 patients) evaluated the impact of DWIT and DAT on biliary complications after liver transplant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not find any difference in readmission rates, PNF rates, early mortality, and hyperbilirubinemia between shorter and longer DAT and DWIT. Moreover, DWIT and DAT did not affect the duration of posttransplant hospitalization and readmission rates that are relevant in terms of hospital costs and resource use in health care . A previous large single‐center study (215 patients) evaluated the impact of DWIT and DAT on biliary complications after liver transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DWIT and DAT did not affect the duration of posttransplant hospitalization and readmission rates that are relevant in terms of hospital costs and resource use in health care. (18,19) A previous large single-center study (215 patients) evaluated the impact of DWIT and DAT on biliary complications after liver transplant. In that study, DWIT and DAT did not affect the rates of posttransplant intrahepatic bile duct strictures and overall biliary complications; only the time from asystole to aortic cross-clamp was associated with increased risk for biliary complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold ischemia time (CIT)is defined as the time in hours from donor liver cross-clamping to cold storage solution removal of the organ [29]. The degree of hepatic fibrosis in all patients included in this study was shown as F4 fibrosis (METAVIR score) at the time of inclusion in the liver transplant waiting list.…”
Section: Liver Function Status In Liver Transplantation Patientsmentioning
confidence: 99%
“…First of all, CIT is acknowledged as one of the most important factors affecting reperfusion injury, liver function recovery, and graft survival. (2) However, CIT was significantly different between the microsteatosis and no steatosis groups (P = 0.002), but it was not listed as one of the variables matched for the 2 groups. This may have resulted in bias in evaluating perioperative and postoperative outcomes.…”
Section: To the Editormentioning
confidence: 88%